Minority Youth: "Big Tobacco's" 21st Century Marketing Targets - Suzanne M Perry-Casler; Apurva Shah; Seraphine Pitt; Ercilia Rodriguez Westhoff; Robert J McDermott (University of North Florida, 2004)
Cigarette smoking and other forms of tobacco use typically begin during adolescence. According to the 2001 Youth Risk Behavior Survey, 33.9% of youth in grades 9 through 12 report recent tobacco use. The tobacco industry spends $9.7 billion annually on marketing. This paper addresses the influence of tobacco marketing, methods to counter the receptivity of tobacco marketing, outcome indicators of Florida's Youth-Focused Tobacco Control Program, and tobacco use among minority youth.